Ultrafine particles in rural and urban dwellings with different household fuel use in developing countries – an example from Pakistan - Nasir, Zaheer A.; Colbeck, I.; Ali, Z.; Ahmed, S. (Pakistan Agricultural Scientists Forum, 2015)
Exposure to indoor particulate matter (PM) is a major public health concern, in particular, in developing countries where solid fuels are typically used as a household energy source. Despite the fact that emission from these fuels can have a dominant fraction of ultrafine particles, exposure to PM is generally characterised in terms of mass concentration of PM10 and PM2.5. The present study was carried out to examine the number concentration of ultrafine particles in rural and urban Pakistani households with different fuels. Air samples were collected from kitchens, living rooms and courtyards of two rural sites (Site I - Solid fuel; Site II - Natural gas) and an urban site (Natural gas) by using condensation particle counters. At rural site - I the 24 hour mean concentration of particles in the kitchen, living room and outdoors was 40,991#/cm(3) (+/- 7472), 30,291#/cm(3) (+/- 13774) and 34,534#/cm(3) (+/- 4947), respectively. During cooking the number concentration can increase significantly with an average hourly maximum value of 169,455#/cm(3). Higher outdoors levels than in living rooms highlight the effect of cooking in open kitchens on ambient levels. At the rural site II the daily average number concentration in living rooms was in the range of 10,745 - 16,126 #/cm(3) with a mean of 13,542 #/cm(3). These values were more than half those in living rooms at rural site I. Whereas in the kitchen the 24hour mean was 27,446#/cm(3) (+/- 4487). At the urban site the mean 24 hour average in the living rooms and kitchens was 45,466 #/cm(3) (+/- 5919) and 65,904 #/cm(3) (+/- 11490), respectively. The 24 hour mean concentration was more than double in the urban kitchens than in rural kitchens at site II. The 24 hour average outdoors was 33,424 #/cm(3) (+/- 6037)-slightly lower than outdoors at rural site I. Overall, the number concentration was higher in kitchens using natural gas fuel at the urban site than in those with solid fuels and natural gas at rural sites. While between rural sites the households with solid fuel had higher concentrations than those with natural gas. Furthermore, outdoors at rural site-I households had higher concentrations as compared to urban household outdoors.
Keywords: Ultrafine particles; Number concentration; Household fuel; Pakistan